The relationship between the adaptive potential of the cardiovascular system and some psychophysiological personality properties in medical students - O. N. Pavlova; A. I. Budaev; D. S. Gromova; S. I. Pavlenko; E. V. Makarova-Gorbacheva; A. V. Ivashchenko (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье)
Adaptive potential is an important indicator of the efficiency of the cardiovascular system. A possible cause of tension in adaptation processes may be situational anxiety, while the question of predictors of its occurrence and its impact on the cognitive abilities of medical students remains incompletely studied.Purpose of the work: to study the relationship between indicators of adaptation of the cardiovascular system and the level of situational anxiety, as well as to analyze individual parameters of attention and social intelligence among second-year medical university students.Object and methods. The study assessed the state of the cardiovascular system, the level of situational anxiety, the level of development of social intelligence and the level of attention in 22 students of both sexes. Results. Adaptation potential is 8.56±0.354 points, which indicates unsatisfactory adaptation of students. Analysis of the index of functional changes showed a satisfactory state of adaptation mechanisms, while 27% of students noted tension in the adaptation mechanisms of the cardiovascular system, which may indicate an excessive influence of stress factors on the functional capabilities of the body. In addition, correlations were identified between: IFI and the level of situational anxiety, situational anxiety and the level of development of social intelligence, and between the indicator of situational anxiety and the duration of work with Schulte tables.Conclusions. The study made it possible to assess the state of students’ adaptation mechanisms and identify the reason for the tension of these mechanisms – the development of anxiety states.